Proses Legislasi dan Implementasi Perda No. 7 Tahun 2023 Kota Bukittiggi dalam Penetapan Kurikulum Muatan Lokal - Julia Salsabila (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Secondary education plays an important role in shaping students' character, skills, and knowledge, as well as being a medium for preserving local culture. This article aims to explain the process of drafting and implementing Regional Regulation No. 7 of 2023 of Bukittinggi City which regulates the local content curriculum. This study uses a case study method with a qualitative approach and a public policy framework. The legislative process is analyzed through six stages: issue identification, agenda setting, political legitimacy, policy formulation, ratification, and implementation. The results of the study show that this Regional Regulation was born from a collaboration between the DPRD, local government, academics, and the community. Initial implementation showed an increase in student participation in local culture-based learning, although still facing challenges in terms of resources and facilities. This Regional Regulation reflects the region's commitment to preserving culture through education and is a model for integrating local values ​​into the formal education system.